Mourtos’s Problem Solving Skills: A View Based on Gender - Yuyun Setyawati; Afandi Afandi; Titin Titin (Universitas Sebelas Maret, 2020)
Problem-solving skill is the ability to solve a problem using the right strategy or procedure. The research aims to analyze student’s mastery of problem-solving evaluated according to gender. Based on Mourtos, Okamoto, & Rhee (2004), there is five problem solving skill indicators: defining the problem, explore the issues, planning the solution, implementing the plan, and evaluating. To obtain the problem-solving skills data using a test consisting of problem description. This research was denveloped through quantitative descriptive analysis to get data by employing a classroom test in grade X MIA II of Muhammadiyah 1 Pontianak, with 29 students of 13 men and 16 women participants. The research finding average results the examinationt of male students at 40 with and SD: 12,5. Whereas, on average, the female student problem-solving skill test result were 45 and SD: 8,8. The obtained percentage of the indicator was that of plan the solution 51,72%, implement the plan 49,14%, explore the problem 41,38%, evaluate 39,66%, and define the problem 32,76%. Based on finding, it can be conclused that problem solving skills in SMA Muhammadiyah 1 Pontianak is still low.